15 Improving equitable enrollment rates in pediatric remote patient monitoring programs. (30th November 2022) - Sump, Courtney; Denker, Kylee; Chapman, DaVona; White, Christine; Riddle, Sarah
Abstract : Background: Remote patient monitoring (RPM) is a form of telemedicine that transmits patient-generated health data to the healthcare team using technology. RPM may detect health problems sooner, breakdown communication barriers, and permit more frequent changes to care plans. Our institution manages ~300 patients/month in 14 RPM programs. Lack of specific inclusion criteria and lack of enrollment analysis allows for disparities in who is offered RPM. Objectives: To Increase percent of eligible patients enrolled in RPM from 83% to 95% by June 2022. Methods: Our interdisciplinary team, including a nurse, physician, quality specialist, data analyst, and family members, aimed to improve RPM enrollment. Using the model for improvement, a high-level process map was developed, as well as a key driver diagram ( figure 1 ). Key drivers included process ownership, clear RPM inclusion criteria, family buy-in, and transparency of enrollment data. Interventions included creating program specific process maps, developing inclusion criteria for new programs, standardizing family communication, and monthly feedback to teams on enrollment successes/failures. Enrollment of eligible patients was tracked on an annotated run chart to assess the effect of our interventions over time. Secondary measures included family satisfaction. Results: Through our interventions, we increased the median percentage of eligible patients enrolled in RPM from 83% to 91% ( figure 2 ). The most common failure of enrollment was due to caregivers with limited English proficiency ( figure 3 ). Family satisfaction was high with 98% caregivers agreeing they would recommend RPM to others. Conclusions: Using QI methods allowed us to increase the percent of eligible patients we enroll in RPM programs at our institution. Next steps include 1) creation of a workflow that allows enrollment of patients with limited English proficiency, and 2) improving adherence with a family-centered focus to meet the needs of our patients.